Mobilitas dan Refleksivitas: Strategi Pemuda Yogyakarta di Masa Transisi menuju Dunia Kerja - Kuslarassakti, Magdalena Putri; Sutopo, Oki Rahadianto (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
This article explains the transition process and youth strategy in Yogyakarta in the era of late modernity. Departing from the context of late modernity in Indonesia, this article applies the concept of mobility as a strategy and reflexive capacity of youth in transition. This article explores the biographical narratives of the four young final-year students in Yogyakarta. By using qualitative methods, this research applies observation techniques and in-depth interviews. The phenomenon of youth studying while preparing for the future, mainly work or/and capital accumulation towards work is a common occurrence of the youth transition in Yogyakarta. Young people respond to the uncertainties of the future and unpredictable consequences of risk through mobility and reflexive capacity as forms of capital. Â Thus, based on empirical data, those two components become essential and valuable wealth to be accumulated by young people.